Pentingnya Kesadaran Masyarakat Terhadap Kekerasan: Strategi Webinar Dalam Perlindungan Dan Mekanisme Pengaduan Bagi Perempuan Dan Anak - Mutmainnah; Yenni Bilolo; Andi Farwatunnisa; Ainun Muflihah Yusuf; Muhammad Nur Hidayat Nurdin; Muhrajan Piara (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The prevalence of issues regarding violence against women and children has become a fairly popular topic in recent years. Violence against women and children in Indonesia continues to occur over time and takes on increasingly diverse forms. Therefore, the protection of women and children has become a primary focus of the Indonesian government. If not addressed seriously, the potential damage to the mental, moral, and spiritual well-being of the younger generation, including children considered as Indonesia's golden generation, may increase due to the significant impact of trauma. The method of implementing activities involves a webinar addressing the topic of "Combating Violence: Protection and Complaint Mechanisms for Women and Children," attended by 40 participants from various backgrounds. It is hoped that with this webinar, the community will be more aware of acts of violence against women and children and can identify indications of criminal acts. Additionally, the webinar is expected to help provide information about complaint mechanisms that can be utilized by the public witnessing acts of violence against women and children, encouraging them to report to the police, especially the Women and Children Protection Unit.